Acute respiratory effects and endotoxin exposure during wheat harvest in northeastern Colorado - Viet, Susan Marie, author; Buchan, Roy, advisor; Stallones, Lorann, advisor; Tucker, Alan, committee member; Bigelow, Philip, committee member; Mielke, Paul W., committee member (Colorado State University. Libraries, 2000)
Acute cross-shift respiratory changes were evaluated at 26 farms in Northeastern Colorado during the summer of 1994 wheat harvest. Trained field staff administered a questionnaire to harvest workers to gather information on respiratory health, past occupational exposures, and smoking status. Each worker was also asked to rank 10 acute symptoms on a scale of 1 to 5 before they began harvest work for the day. Spirometry was performed immediately after the questionnaire was completed using NIOSH's HF5 spirometric system. Each participant wore a high flow personal air sampling pump with a 35-mm, closed-face cassette and fiber glass filter. Participants were observed throughout the workshift to determine tasks performed and personal protective equipment worn. At the end of the workshift, spirometry and ranking of the 10 acute symptoms were conducted again. Total dust exposure was determined gravimetrically. Total endotoxin was measured by the Limulus amoebocyte lysate (LAL) assay. The 98 harvest workers included in the study ranged in age from 18 to 80 years. The gender distribution included 90 males and 8 females. Ten percent of the workers had airway obstruction, as indicated by the pre-shift spirometry test results. Fifty percent of the workers were smokers or ex-smokers. Tasks included combine operators, auger operators, grain truck drivers, grain cart drivers, and supervisors. Total dust exposures ranged from 0.09 to 15.33 mg/m3 (geometric mean 0.83 mg/m3), with 8 percent of workers exposed above the threshold limit value of 4 mg/m3. Total endotoxin exposures ranged from 4.4 to 744.4 EU/m3 (geometric mean 54.2 EU/m3), with 33 percent of workers exposed above levels associated with symptoms and lung function effects. At these exposure levels, 60 percent of workers experienced a cross-shift change in at least one respiratory symptom. The respiratory index (sum of cross-shift change in eight acute respiratory symptoms) was significantly correlated with both total dust and endotoxin exposure. Peak expiratory flow rate was found to decrease over the workshift in a manner similar to that experienced by cotton workers. Cross-shift changes in the spirometric variables were associated with smoking status, age, presence of airway obstruction, and history of chronic respiratory symptoms, but not with dust or endotoxin exposure. This study is the only known study that has examined cross-shift symptom and lung function change and dust and endotoxin exposure during harvest activities, which may be applicable to workers in other agricultural settings.
Keywords: toxicology